A holistic model of human capital for value creation and superior firm performance: The Strategic factor market model - Ebes Esho; Grietjie Verhoef (Cogent Business & Management, 2020)
Understanding the link between human capital, competitive advantage and firm performance is a major focus of research in strategic human capital studies in strategic management and Strategic Human Resource Management (SHRM). Indeed, much progress has been made in understanding this link. However, strategy scholars have emphasized firm-specific human capital as the most strategic form of human capital, and mobility constraints as the route to human capital-based competitive advantage and superior performance. SHRM, on the other hand, have been primarily focused on human resource policies, practices and systems, and more recently on the ability, motivation, and opportunity framework. Consequently, there has been an implicit assumption that there is already an understanding of how human capital actually creates value in firms. This article presents a succinct review of extant studies and a model that explores value creation from human capital. The model, based primarily on the theory of strategic factor market, holds promise in furthering extant understanding of the link between human capital, competitive advantage and firm performance. The model takes a more holistic approach to the role of human capital in value creation in firms.
Keywords: 650; human capital; strategic factor market; knowledge; competitive advantage; value creation; value capture